Comparison of the influence of Cu micro- and nano-particles on the thermal properties of polyethylene/Cu composites (eXPRESS Polymer Letters, 2009)
Polyethylene (LDPE, LLDPE and HDPE) composites with different copper (micro- and nano-sized particles) contents were prepared by melt mixing and compression moulding. The melting and crystallization behaviour of the different composites was analysed using a differential scanning calorimeter (DSC), and the thermal stability in a thermogravimetric analyser (TGA). The thermal conductivities of the samples were also determined. The DSC results show that the Cu micro- and nano-particles influence the crystallization behaviour of the polyethylenes in different ways. The extent to which the copper particles influence the crystallization behaviour of the polyethylenes also depends on the respective morphologies of the different polyethylenes. The TGA results show an observable influence of both the presence of copper and the sizes of the copper particles on the thermal stabilities of the polymers. Thermal conductivities increased with increasing Cu content, but there was little difference between the thermal conductivities of the samples containing Cu micro- and nano-particles.